Are Aqidah Akhlak Teachers In Private Madrasahs More Creative than Those in Public Madrasahs? A Case Study - Lukman; Muna, Rochmatul; Safitri, Marcelina Via Hanadya; Mubarokhah, Lailatul (el-Tarbawi, 2024)
Moral education plays a crucial role in shaping student characteristics. The lack of creativity in teaching Aqidah Akhlak poses a barrier to effective character development. Therefore, this study analyzed the creativity of teachers in teaching Aqidah Akhlak in public and private senior high schools. This study employs a qualitative approach using a case study method. The research participants were six Aqidah Akhlak teachers, 12 students from two public Islamic senior high schools, and four private Islamic senior high schools in Bantul Regency, Indonesia. The results indicate that teacher creativity in teaching Aqidah Akhlak is more prominent in private schools than in public schools. Teachers in priate schools show better performance in developing creative learning strategies, presenting more interesting material, and creating a more interactive learning environment so that students can be actively involved in the learning process, understand religious values, and internalize them in their daily lives. One creative approach that resonates with students is the "confide-in" session during lessons, which boosts their enthusiasm and encourages positive behavior.